Advanced Manufacturing of Patient‐Specific Occluders for the Left Atrial Appendage with Minimally Invasive Delivery. Issue 5 (29th March 2020) - Alaie, Seyedhamidreza; Robinson, Sanlin S.; Amiri Moghadam, Amir Ali; Augé, Jordyn; Caprio, Alexandre; Kolli, Kranthi; Al'Aref, Subhi J.; Min, James K.; Mosadegh, Bobak; Dunham, Simon
Abstract : A novel method for the rapid prototyping of personalized inflatable left atrial appendage occluders, suitable for minimally invasive delivery, is demonstrated. The method allows for the design, fabrication, and quantitative testing of implants based on an individual's computed tomography (CT) scan. The performance of a left atrial appendage occluder by characterizing its ability to anchor, prevent leaks, and not obstruct the left atrium is reported on. The design of the occluder by varying features such as size, inflation fluids, and surface patterns is optimized. The implant, and its delivery via a minimally invasive catheter, is demonstrated in a 3D‐printed left atrial model. Herein, the way for leveraging advanced manufacturing and imaging technologies for the development of personalized intracardiac implants for transcatheter delivery is described. Abstract : Novel strategies for creating thin walled inflatable patient‐specific left atrial appendage occluders are explained. Herein, a patient's CT image is used to define a custom geometry. Rapid prototyping from thin walled medical polyurethanes with custom surface micropatterns allow for designs that are compatible with catheter deployment.